KONTRUKSI MAKNA TRADISI PEUSIJUEK DALAM BUDAYA ACEH - Chaerol Riezal; Hermanu Joebagio; Susanto Susanto (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2018)
This paper answers the question of how the construction of the meaning of the Peusijuek tradition is available in Aceh culture. Two important things that will support this thesis is how the mind and culture of Islam and Aceh combined into one formulated in a way. Therefore, how the processes, forms and philosophical meanings of the Peusijuek tradition available in Aceh culture will be discussed in this paper. The results of this study indicate that the Peusijuek tradition is one of the relics of Hindu Culture in Aceh. According to historical records, the implementation of the Peusijuek tradition before the sending of Islam still uses certain mantras and prayers. However, since the arrival and development of Islam in Aceh, the Peusijuek tradition has been changed by incorporating Islamic teachings in it, such as prayer, prayer, and other Islamic teachings. That is why the Peusijuek tradition in Aceh can still be up to now. In practice, the Peusijuek tradition is carried out by religious leaders and elders of Aceh, such as ulama, tengku, ustadz and ustadzah. This is done because the Peusijuek tradition is considered a sacred Acehnese procession. The practice of Peusijuek tradition in Aceh is carried out in religious and cultural activities, such as performing pilgrimage, marriage, circumcision, prayer, arena, buying new vehicles, and so forth. The purpose of this Peusijuek tradition is to appeal for the satisfaction, peace, happiness, and glory of the guests.